AN ANALYSIS OF THE PERFORMANCE AND EFFECTIVENESS OF POLITICAL STRATEGIC LEADERSHIP IN INDONESIA - Arman, Arman; Patasaka, Rini Indryati (JWP (Jurnal Wacana Politik), 2024)
The purpose of this study is to analyze the performance and effectiveness of political policy strategies in Indonesia using a quantitative research method with a snowball sampling technique with a sample size of 1,200 respondents from 38 provinces. margin of error of approximately 5 percent at a 95 percent confidence level with descriptive statistical data techniques where the data used to describe or summarize the main characteristics of the analysis of performance and effectiveness of political strategy leadership in Indonesia, the data tool uses SPSS statistics version 26, with a time of 2 years, with the results of the analysis of performance and effectiveness of political strategy leadership in Indonesia where scientific selection and training of workers, the role of civil society, political parties, the military, and do not know with an average of 86%.